Pax3/7 regulates neural tube closure and patterning in a non-vertebrate chordate - Kim, Kwantae; Orvis, Jameson; Stolfi, Alberto (Frontiers in Cell and Developmental Biology, 2022)
Pax3/7 factors play numerous roles in the development of the dorsal nervous system of vertebrates. From specifying neural crest at the neural plate borders, to regulating neural tube closure and patterning of the resulting neural tube. However, it is unclear which of these roles are conserved in non-vertebrate chordates. Here we investigate the expression and function of Pax3/7 in the model tunicate Ciona. Pax3/7 is expressed in neural plate border cells during neurulation, and in central nervous system progenitors shortly after neural tube closure. We find that separate cis-regulatory elements control the expression in these two distinct lineages. Using CRISPR/Cas9-mediated mutagenesis, we knocked out Pax3/7 in F0 embryos specifically in these two separate territories. Pax3/7 knockout in the neural plate borders resulted in neural tube closure defects, suggesting an ancient role for Pax3/7 in this chordate-specific process. Furthermore, knocking out Pax3/7 in the neural impaired Motor Ganglion neuron specification, confirming a conserved role for this gene in patterning the neural tube as well. Taken together, these results suggests that key functions of Pax3/7 in neural tube development are evolutionarily ancient, dating back at least to the last common ancestor of vertebrates and tunicates.